Impact of natural aging on the physical and pasting properties of Indonesian Ciherang rice during storage - Cahyana, Purwa Tri; Sunarti, Titi Candra; Hardjomidjojo, Hartrisari; Noor, Erliza; Laily, Noer (Journal of Food Technology Research, 2026)
Natural aging induces substantial variations in the properties of rice during extended storage periods. This study compared the changes in the texture and paste profile of local Indonesian Ciherang rice varieties stored at room temperature for 0, 12, 24, 36, and 48 months. Texture Profile Analysis (TPA), Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and Rapid Visco Analysis (RVA) were used to compare the changes in texture, structure, and pasting characteristics. The TPA results showed an increasing trend in hardness, cohesiveness, springiness, and chewiness, indicating starch retrogradation and enhanced intermolecular interactions. FTIR spectra revealed decreased intensities of –OH and carbonyl groups, indicating water loss and the degradation of lipid/protein molecules. XRD confirmed the retention of A-type crystallinity without polymorphic transformation, indicating morphological stability despite prolonged storage periods. The RVA profile demonstrated a reduction in peak and breakdown values and an overall increase in the setback and final viscosities up to 24 months, reflecting the high retrogradation and reduced water absorption capacity of the samples. The reduction in final viscosity at 36 months indicated molecular breakdown and a less stable gel network. Overall, long-term atmospheric storage qualitatively alters the texture and viscoelasticity of rice. These findings underscore the importance of monitoring rice aging to improve storage strategies, optimize industrial processing, and ensure consumer acceptance of aged rice products.